Russian industrial production development - A. K. Titov (Вестник университета, 2023)
The study assesses main factors affecting successful processes of industrial production in Russian regions in recent times. It considers the unfavorable effects of the pandemic and sanctions on industrial enterprises production. The discussion centers on the examination of industrial production in modern Russia and forecasting its further development. The introduction presents a review of scientific literature of financial experts and researchers studying the phenomena of industrial production. The purpose of the study is to examine the state of industrial production development in Russia considering regional economic evolution under sanctions. An exhaustive assessment of the factors determining industrial development, as well as main economic indicators of industrial companies’ performance, has been carried out. The article also includes a study of the works of scientists who participated in assessing this issue from both domestic and foreign points of view. Special attention has been paid to the factors that characterize the industrial production cycle in Russia and its regions. In conclusion, the author summarized the results of the conducted research and review of scientific materials. The essence of this generalization is to endorse continuous transformation of regional industrial production management in the future. Proposals for sustainable development of industrial production in the long term have also been put forward.